Rethinking reproductive "tourism" as reproductive "exile" - Inhorn, Marcia C; Patrizio, Pasquale (Fertility and sterility, 2009)
Whereas reproductive "tourism" implies leisure travel, reproductive "exile" bespeaks the numerous difficulties and constraints faced by infertile patients who are "forced" to travel globally for assisted reproduction. Given this reality, it is time to rethink the language of "reproductive tourism," replacing it with more accurate and patient-centered terms.